PENGARUH UPAH TERHADAP MOTIVASI KERJA KARYAWAN HOME INDUSTRY GAMELAN MITRA JAYA MAGETAN - Nisa Nur Hidayah (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to determine the remuneration to the home industry Gamelan Mitra Jaya Magetan, to know the motivation of employees working at home industry Gamelan Mitra Jaya Magetan as well as to determine whether or not the influence of remuneration on employee motivation Mitra Jaya Magetan homeindustry. This research is a descriptive study using quantitative methods, data obtained from population samples were analyzed according to the statistical methods used then interpreted. In this research, data collection techniques used by researchers is a questionnaire or questionnaires, observation, and documentation. The population in this study is the overall employees who are in the home industry Gamelan Mitra Jaya Magetan the period March 2015 to May 2015. The sampling technique used is saturated sample in which all the population sampled, namely some 35 employees. These results indicate that the wage is given less good can be seen from the results of the average is equal to 30,31. This happens due to other factors that affect include: the ability of workers, co-workers, supervision, praise, the work itself. T test calculation results obtained tcount results (9.9076) ≥ ttab (1.66691) This situation can be said to be no different wage effect on employee motivation in the home industry Gamelan Mitra Jaya Magetan. It can be concluded that the wage effect on employee motivation in the home industry, Mitra Jaya Magetan.